The beginnings of Caesar (Octavius) as a military commander: The year 44, from Apollonia to Rome, according to Nicolaus of Damascus, ???? ???????? - Sabino PEREA YÉBENES (Studia Historica: Historia Antigua, 2016)
After the Ides of March 44 BC Octavius goes to the political scene, at 19 years old. We follow the story of the ???? ???????? written byNicolaus of Damascus, witnessing the rise of the young Caesar, from hisstay in Apollonia (on March 44) until his departure for Rome at the end of the same year. For the first time it is put in command of a large private army. The story of Nicolaus is very close to the facts; and though as a whole it is a eulogy of young, completes the story of complicated Year 44 in the writings of Appian, Dio Cassius and the speeches and letters of Cicero.